Encapsulation and subjectivity from the standpoint of viewpoint theory. (23rd March 2022) - Morsella, Ezequiel; Velasquez, Anthony G.; Yankulova, Jessica K.; Li, Yanming; Gazzaley, Adam
Abstract: The groundbreaking, viewpoint theory of Merker et al. explains several properties of the conscious field, including why the observer cannot directly apprehend itself. We propose that viewpoint theory might also provide a progressive, constitutive marker of consciousness and shed light on why most of the contents of consciousness are encapsulated.